The Internet and Changes in the Media Industry: A 5-Year Cross-National Examination of Media Industries for 51 Countries. (September 2019) - Ji, Sung Wook
This study explores the effects of the Internet on changes in traditional media industries. Previous studies addressing the Internet's effects on media industries have largely been conducted in a piecemeal fashion, with most tackling narrowly defined topics limited to individual media in specific countries. By taking a broader perspective on the Internet's effects, this study examines changes in the aggregate revenue of all major media industries. Employing country-level, panel-data analysis of 51 countries from 2009 to 2013, the study shows that the Internet has led to a shift in the balance of revenue away from advertising and toward direct payments.